Uncovering The Treasure Of Women Empowerment Through The Education Among The Tai Khampti People Of Arunachal Pradesh (Journal of Namibian Studies : History Politics Culture, 2023)
Women empowerment is the multifaceted concept in the contemporary world. The Tai Khampti tribe is one of the major tribe of Arunachal Pradesh. One general conception is that the tribal society women are more marginalized and educationaly backward rest of the other society. In the Tai Khamti society most of the women are educated and all the women are  very hardworking. In this study try to discuss the educational and employment status of women in the Tai Khamti society. Apart from that it also try to find out the relation between education and empowerment of the Tai khamti women in ArunachalPradesh.This study completely based on primary sources of data collection.